THE INFLUENCE OF THE IMPLEMENTATION OF E-TENDERING ON THE COMPETITIVENESS OF SMALL AND MEDIUM ENTERPRISES IN CONSTRUCTION INDUSTRY - Oleksandr Sydorenko (Izdevnieciba "Baltija Publishing", 2017)
The rapid pace of technological progress during the last years has influenced the construction industry greatly. Due to the increasing electronic integration of the construction processes, the participants have no choice but to embrace all the latest electronic technologies. The E-tendering system was introduced with the aim to provide higher transparency in each stage and transaction of a procurement process, as well as to reduce paperwork. However, the successful implementation of the information and communication technologies, such as E-tendering, requires the particular attention and great effort from the companies. This article identifies the main trends in construction industry regarding electronic technologies and potential benefits that participants can gain from implementing E-tendering system.